Wearable antennas and filters design - Lim, Yi Liang (2015)
Existing designs of antennas and filters from different papers were looked at and among them two filters [3],[4] and an antenna [2] are referenced to for this project. The designs are first replicated using Advanced Design System (ADS) software to achieve as similar as possible simulated results. Next, modifications are made to observe the effects on the S-parameters output to gain a general understanding of how the layout changes affect the performance of the antennas and filters. The substrates are then swapped with a cloth substrate from [1] with εr = 2.4, Tan D =0.0048. The resultant output is then further tuned with the previous knowledge gained from modifying the layout dimensions by using ADS Linecalc to attempt to attain a near similar output with the reference material. This is to find out the viability of using a cloth substrate on existing designs and the problems of such a migration.